PENERAPAN MEDIA VIDEO TUTORIAL PEMBUATAN POLA DASAR SISTEM PORRIE MULIAWAN PADA SISWA KELAS X TATA BUSANA DI SMKN RENGEL TUBAN - Salsabila Rahmadani; Imami Arum Tri Rahayu (JURNAL ILMIAH NUSANTARA, 2026)
This study aimed to describe the feasibility of a tutorial video as a learning medium for constructing basic patterns using the Porrie Muliawan system and to describe students' learning outcomes after its implementation. This study employed a quantitative descriptive approach involving 36 tenth-grade students of the Fashion Design Program at SMKN Rengel Tuban. The research instruments consisted of media and material validation sheets and a student learning achievement test. The data were analyzed descriptively by calculating the average feasibility scores and the percentage of students achieving learning mastery. The results showed that the tutorial video obtained a feasibility score of 91.33% from the media expert and 94.67% from the material expert, both categorized as highly feasible. The students' learning outcomes showed an average score of 83.6, with a classical learning mastery of 86.11%, indicating that 31 out of 36 students achieved the Minimum Mastery Criterion (MMC). These findings indicate that the tutorial video helped students understand the steps of constructing basic patterns using the Porrie Muliawan system more clearly and systematically, thereby supporting improved learning outcomes. Therefore, the tutorial video can be used as an effective alternative learning medium in pattern-making courses for the Fashion Design Program.